Teaching Factory (TeFa) Learning Strategy and Risk Management at SMK Negeri 1 Garut - Pratiwi, Ratih; Cahyana, Agus; Sastrawan, Uding; Pratama, Aldi Adi (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
Absorption of SMK graduates in the world of work is said to still beproblem crucia lTeFa learning at SMK Negeri 1 Garut by producing products/services resulting from student learning and the use of products/services by the community. Competence  in Accounting and Financial Institutions (AKL) of SMK Negeri I Garut is still transforming towards the implementation of TeFa learning. The research methodology used includes a population consisting of students involved in TeFa, TeFa administrators, and educators. Data were obtained through questionnaires, observations and focus group discussions; and this research is a descriptive study using the SWOT analysis method and risk management review on the TeFa component. The results of the study indicate that the development TeFa learning uses a strength-opportunity of approach with moderate risk analysis results. The implication of implementing the (Strength-Opportunity) strategy is to accelerate the implementation of TeFa learning and have the impact of producing according to market